Hubungan Kepatuhan Konsumsi TTD, Asupan Zat Gizi, dan Status Gizi Terhadap Kejadian Anemia pada Remaja Putri Di SMPN 1 Gunungsari: Hubungan Kepatuhan Konsumsi TTD, Asupan Zat Gizi, dan Status Gizi terhadap Kejadian Anemia pada Remaja Putri di SMPN 1 Gunungsari - Abby, Sekarmirah Octila; Arini, Firlia Ayu; Sufyan, Dian Luthfiana; Ilmi, Ibnu Malkan Bakhrul (Amerta Nutrition, 2023)
Background: Female adolescents are a group that is prone to having anemia because they are in the second growth spurt phase and experience menstruation monthly. Anemia in young women causes a detrimental effect. The increase in prevalence of anemia can be prevented and reduced by iron supplementation in women of reproductive age, including female adolescents. Objectives: This study aims to determine the relationship between the compliance of iron supplement consumption, nutrient intake, and nutritional status with the incidence of anemia in female adolescents at SMPN 1 Gunungsari. Methods: This study used a cross-sectional design. The research population was female students at SMPN 1 Gunungsari, totaling 290 female students. The sample in this study was selected using a stratified random sampling method, totaling 61 respondents. The data collection used Hb examination, SQ-FFQ form, and anthropometric examination. Analysis of the relationship used the Chi-Square test and Fisher's Exact. Results: The results of this study showed that there was a relationship between the compliance of iron tablets consumption (p=0.002), protein intake (p=0.034), and iron (p=0.046) with the incidence of anemia, and there was no relationship between intake of vitamin C (p=0.139), iron inhibitors (p=0.183), and nutritional status (p=1.000) with the incidence of anemia in female adolescents at SMPN 1 Gunungsari. Conclusions: This study concludes that there is a relationship between compliance to iron supplement consumption, protein, and iron intake with the incidence of anemia, and there is no relationship between intake of vitamin C, iron inhibitors, and nutritional status with the incidence of anemia.